The assessment of thrombotic markers utilizing ionic versus non‐ionic contrast during coronary angiography and intervention trial. Issue 5 (16th January 2016) - Shah, Binita; Berger, Jeffrey S.; Allen, Nicole; Guo, Yu; Sedlis, Steven P.; Xu, Jinfeng; Perez, Adriana; Attubato, Michael; Slater, James; Feit, Frederick
Abstract : Objective: To determine how two different types of iodinated contrast media (CM), low‐osmolar ionic dimer ioxaglate (Hexabrix) and iso‐osmolar non‐ionic dimer iodixanol (Visipaque), affect multiple indices of hemostasis. Background: In vitro models demonstrate differential effects of ionic and non‐ionic CM on markers of hemostasis. Methods: This blinded endpoint trial randomized 100 patients to ioxaglate or iodixanol. The primary endpoint was change in endogenous thrombin potential (ETP) following diagnostic angiography. Secondary endpoints included change in markers of fibrinolysis [tissue plasminogen activator (tPA) and plasminogen activator inhibitor 1 (PAI‐1)] and platelet aggregation following diagnostic angiography and percutaneous coronary intervention (PCI) with bivalirudin. Data are presented as median [interquartile range]. Results: ETP significantly decreased after diagnostic angiography in both ioxaglate (baseline 1810 nM*minute [1540‐2089] to post‐angiography 649 nM*minute [314‐1347], p  < 0.001) and iodixanol groups (baseline 1682 nM*minute [1534‐2147] to post‐angiography 681 nM*minute [229‐1237], p  < 0.001), but the decrease was not different between CM ( p  = 0.70). There was a significant increase in ETP during PCI ( n  = 45), despite the use of bivalirudin, suggesting a prothrombotic effect of PCI (post‐angiography 764 nM*minute [286‐1283] to post‐PCI 1081 nM*minute [668‐1552], p  = 0.02). There were no significant differential effects on tPA, PAI‐1, and markers of platelet activity. Conclusion: There were no significant differential effects between ioxaglate and iodixanol. Both CM led to significant reductions in thrombin generation and no significant effects on fibrinolytic activity or platelet activity, thereby contributing to a favorable antithrombotic milieu. © 2016 Wiley Periodicals, Inc.